A trial case of medical treatment for primary headache using telemedicine. Issue 9 (March 2018) - Akiyama, Hisanao; Hasegawa, Yasuhiro
Abstract: Rationale: Video-based treatment in telemedicine is a potential alternative to face-to-face treatment. We describe our trial use of telemedicine to treat a patient with primary headache. Patient concerns: A 25-year-old woman visited our branch hospital with a chief complaint of recurrent headache. Our branch hospital had no headache specialist, so a headache specialist at our main hospital provided treatment remotely. Diagnoses: She was diagnosed with migraine without aura by the headache specialist using telemedicine. Interventions: The branch hospital physician and the headache specialist used video conferencing to interview and examine the patient and share cranial magnetic resonance imaging (MRI). Audio and camera angle/zoom could be adjusted during interviews, and high-quality video was continuously displayed at both hospitals simultaneously without lag between audio and video. Temporal/spatial resolution was sufficient for proper neurological evaluation. MRI had sufficient image quality and resolution for detailed interpretation. A prescription for medication was issued by the branch hospital physician and confirmed by the headache specialist. Outcomes: Zolmitriptan was effective in treating her migraine. Lessons: Telemedicine was useful for treating this primary headache patient and can contribute to regional health care. Future challenges in telemedicine include expanding its use to other areas within the purview of general physicians and headache specialists, covering implementation and maintenance costs, providing adequate explanations to patients and family members, ensuring security of video transmissions, maintaining patient medical records, and supervising treatment.